Monitoring of athletes condition: Male handball players body part pain in handball performance - Mukta, Fatima Tus Johora; Rickta, Jannatul Ferdaus; Arafat, Md. Yeasir (Journal of Sports Research, 2025)
Handball is a globally popular sport that requires frequent jumping, landing, and rapid directional changes, often resulting in pain or physical discomfort among players. This study observed 13 national-level male handball players during a training camp to assess the impact of body part pain on performance. Pain was monitored over four consecutive days during the second daily practice session. A Visual Analog Scale (VAS) was used to evaluate both pain in specific body parts and self-rated performance aspects such as satisfaction and concentration. Linear mixed modeling was applied to analyze the relationship between pain and performance, accounting for daily individual variation. The results revealed that several players reported high VAS pain scores in the dominant shoulder and elbow, while one athlete reported a maximum score of 10 in the dominant knee. Pain in the ankle joints was also notably high. This study highlights the importance of monitoring physical discomfort during training, as pain in key joints may negatively affect both perceived and actual handball performance.